Elf-1 Contributes to the Function of the Complex Interleukin (IL)-2–responsive Enhancer in the Mouse IL-2 Receptor α Gene - Serdobova, Irina (The Rockefeller University Press, 1997)
Lymphocytes regulate their responsiveness to IL-2 through the transcriptional control of the IL-2Rα gene, which encodes a component of the high affinity IL-2 receptor. In the mouse IL-2Rα gene this control is exerted via two regulatable elements, a promoter proximal region, and an IL-2–responsive enhancer (IL-2rE) 1.3 kb upstream. In vitro and in vivo functional analysis of the IL-2rE in the rodent thymic lymphoma-derived, CD4(−)CD8(−) cell line PC60 demonstrated that three separate elements, sites I, II, and III, were necessary for IL-2 responsiveness; these three sites demonstrate functional cooperation. Site III contains a consensus binding motif for members of the Ets family of transcription factors. Here we demonstrate that Elf-1, an Ets-like protein, binds to site III and participates in IL-2 responsiveness. In vitro site III forms a complex with a protein constitutively present in nuclear extracts from PC60 cells as well as from normal CD4(−)CD8(−) thymocytes. We have identified this molecule as Elf-1 according to a number of criteria. The complex possesses an identical electrophoretic mobility to that formed by recombinant Elf-1 protein and is super-shifted by anti–Elf-1 antibodies. Biotinylated IL-2rE probes precipitate Elf-1 from PC60 extracts provided site III is intact and both recombinant and PC60-derived proteins bind with the same relative affinities to different mutants of site III. In addition, by introducing mutations into the core of the site III Ets-like motif and comparing the corresponding effects on the in vitro binding of Elf-1 and the in vivo IL-2rE activity, we provide strong evidence that Elf-1 is directly involved in IL-2 responsiveness. The nature of the functional cooperativity observed between Elf-1 and the factors binding sites I and II remains unresolved; experiments presented here however suggest that this effect may not require direct interactions between the proteins binding these three elements.